Power Quality Problem In Iraqi Network And Its Mitigation Techniques - Mohammed Saleh AL-MAHMOOD; Ramazan Nejat TUNCAY (Genius Journals, 2022)
Globally, the reliability of electricity networks is becoming a significant concern. The electrical grid must provide sinusoidal voltages and currents that are unvarying in frequency and amplitude. However, connecting non-linear loads causes harmonics to be produced, which lowers the grid's quality. Harmonics in load currents can cause several detrimental effects, including distortion of the voltage waveform at the point of common coupling. Therefore, harmonics must be reduced in order to maintain good grid quality. In this study, a brief information about the Iraqi power system is presented, and the non-linear load is connected on to 132 kV Hamam Al-aleel substation. The harmonics and its major impact on power systems with reference to harmonic distortion brought on by non-linear loads are discussed. The study show that when passive filters are used in parallel with the non-linear load, the harmonics in current waveform can be reduced and substantially enhance the power quality of the system
Keywords: Power Quality; Harmonics; Passive Filters; Iraqi Power System